Immunoliposomes for Alzheimer's Disease Therapy Nanocarriers to cross the blood-brain barrier and bind to amyloid beta-peptide - J. A. loureiro (2013)
There have been several efforts to understand the etiology of Alzheimer's disease (AD) and to find the cure for such debilitating disease. Despite the efforts, there is still no cure or effective treatment for AD. Many reasons contribute for such disappointing outcome, being one of them the fact that the transportation through the blood-brain barrier (BBB) remains an obstacle. Immunoliposomes are drug carriers that can be used to encapsulate and to deliver drug molecules through biological membranes as the BBB. In the present work, the integrity of immunoliposomes coated with monoclonal antibodies (mAb) against endogenous receptors of the BBB was studied by different techniques including cryo-scanning electron microscopy and dynamic light scattering.